Stochastic Linear Programming Method for Housing Investment Feasibility in West Jakarta - Frenki; Mark Setiadi; Waty Asriningsih Pranoto (Jurnal Ilmiah Dinamika Rekayasa, 2024)
This research was conducted in light of a planned investment for residential housing construction in West Jakarta, given the minimal availability of land in the area in terms of land size, price, shape, and other factors, necessitating an investment feasibility study. The purpose of the investment feasibility study is to analyze the viability of this investment. Besides the limited land availability, there is often uncertainty during the sales stage. Thus, this study employs a two-stage stochastic programming model. The houses to be built are divided into two types: houses with a width of 4 meters and houses with a width of 4.5 meters. The two-stage stochastic programming model created consists of 2 stages: stage 1 during housing construction and stage 2 during sales. The objective function is to get the maximum net present value (Zmax). The overall time required for this investment is 4 years. After creating a two-stage stochastic programming model, the analysis was carried out using the Solver Add-in in Microsoft Excel. The analysis concluded that the maximum net present value expected in this investment is 4,092.036 million Rupiah; with a positive net present value, this investment is acceptable. This analysis was added with the calculation of IRR as a supporter of the net present value, resulting in an interest rate of 23.63%. Given a large enough IRR, it can be concluded that this housing development investment is acceptable.